Encryption processing over communication network - Zhang, Anqi (2016)
Abstract Wireless LAN has turned out to be more predominant these days. It has been expanding in numerous places, such as enterprises, institutions or even restaurant and cafes. Wireless LAN provides mobility and convenience to people, but at the same time it is exposed to many security threats due to its wireless infrastructure. The objective of this final year project is to study and evaluate the existing security threats against wireless LAN. The basic security standards were studied and tested. VPN technology and cryptography were also studied due to nowadays network architecture. A communicator program named crypto file transport were developed to ensure secure transfer of files through the wireless infrastructure on top of existing security standards. Diffie-Hellman algorithm and Advanced Encryption Standard(AES) were used to develop the communicator program. The program was developed using Java programming language. It was created using Java Development Kit 1.8 and IntelliJ IDEA IDE. Overview of the project and the existing security standards were discussed in chapter 1. The concept and types of VPN technologies were elaborated in chapter 2. Chapter 3 covers the concept and working mechanism of different encryption algorithms. The implementation of the communicator program was discussed in chapter 4 and the results of the program were shown in the last chapter.